2011
DOI: 10.1007/s00251-011-0540-x
|View full text |Cite
|
Sign up to set email alerts
|

KIR gene diversity in Mexican mestizos of San Luis Potosí

Abstract: Natural killer (NK) cell function is regulated by different types of membrane-bound receptors of which killer-cell immunoglobulin-like receptors (KIRs) are the most complex and diverse. KIRs are encoded by 17 different genes located within the leukocyte receptor complex (19q13.4). The frequency with which KIR gene features are present in different human populations differs. Here, we present our results on the KIR gene diversity observed in a large group of mestizos from the central Mexican city of San Luis Pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 79 publications
1
9
0
Order By: Relevance
“…Alvarado has analyzed 60 human populations phylogeny based on activating KIR gene frequencies. All populations have been clustered to six clades: East Asian, Arab/Caucasoid, Mexican mestizo/Amerindian and South Asian, African [29]. In our PCA results, East Asian and Caucasoid also clustered respectively, whereas Mongolian was not gathered to neither East Asian nor Caucasoid populations, has similar genetic distances to east Asian or Caucasoid clades in genetic trees.…”
Section: Discussionsupporting
confidence: 44%
“…Alvarado has analyzed 60 human populations phylogeny based on activating KIR gene frequencies. All populations have been clustered to six clades: East Asian, Arab/Caucasoid, Mexican mestizo/Amerindian and South Asian, African [29]. In our PCA results, East Asian and Caucasoid also clustered respectively, whereas Mongolian was not gathered to neither East Asian nor Caucasoid populations, has similar genetic distances to east Asian or Caucasoid clades in genetic trees.…”
Section: Discussionsupporting
confidence: 44%
“…The frequency of the NKG2C deletion in our population was assessed with the use of DNA samples belonging to the Mexican Reference Genomic DNA Collection (MGDC‐REF) which is composed of 300 healthy donors (Alvarado‐Hernández et al ., ). For the case–control association study, patients with virologically confirmed respiratory syncytial virus (RSV) ( n = 61), and pandemic A (H1N1) 2009 influenza ( n = 70) infections were included.…”
Section: Methodsmentioning
confidence: 97%
“…KIR, HLA-B public epitope typing and broad HLA-C group 1 or 2 typing were performed using previously published SSP-PCR-based strategies (Alvarado-Hernandez et al 2011;Bunce et al 1995;Hiby et al 2008). Our KIR genotyping approach does not discriminate between KIR2DL5A and 2DL5B or the centromeric or telomeric localization of KIR2DS3, 2DS5 and 2DL5A/B.…”
Section: Methodsmentioning
confidence: 99%
“…This admixture occurred soon after the Spanish conquest of 1521 and has also been influenced, to a lesser extent, by recent human migrations (Alvarado-de la Barrera et al 2000). KIR and HLA traits in Mexican mestizos have been shown to be different from those present in other human groups (Alvarado-Hernandez et al 2011;Contreras et al 2007;Vargas-Alarcon et al 2010). More importantly, the distribution of Bw4-bearing HLA-B alleles in the Mexican mestizo population is different to that of Caucasoids, see Table 1.…”
Section: Introductionmentioning
confidence: 94%